Lantana calcicola: a new and threatened Verbenaceae species from Lajedão, a limestone outcrop in northern Minas Gerais state, Brazil - Cardoso, Pedro Henrique; Silva, Gabriel Barros Da; Melo, Pablo Hendrigo Alves De; Salimena, Fátima Regina Gonçalves; Silva, Tânia Regina Dos Santos (Phytotaxa, 2025)
A comprehensive analysis of Lantaneae specimens from Brazil has unveiled a new species with fleshy fruits, belonging to Lantana (a non-monophyletic genus). Named Lantana calcicola, this species was discovered in northern Minas Gerais state, within the Caatinga domain, growing on an open karst formation in the municipality of Matias Cardoso, locally referred to as Lajedão. The new species is a subshrub, with unarmed branches, conspicuously petiolate leaves, narrowly lanceolate to linear bracts, white corollas, and conspicuous fleshy fruits. A detailed description, illustrations, comparisons with morphologically similar and sympatric species, plus a geographic distribution map are provided. Based on the IUCN criteria, this species can be currently assessed as Critically Endangered (CR). Notably, this is the second Verbenaceae species recently described from Lajedão, highlighting the critical importance of conserving this unique and floristically important ecosystem.